Penerapan Project Based Learning dalam Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam (PAI) di Kelas VC SD Negeri 13/I Muara Bulian dengan Menggunakan Metode Tanya Jawab - Muthaharo, Pityatul; Pitnizar, Pitnizar; Halimah, Siti (ISLAMIKA, 2025)
This research aims to explore the implementation of Project Based Learning (PjBL) combined with the question-and-answer method in improving student learning outcomes in Islamic Religious Education (PAI) for class VC at SD Negeri 13/I Muara Bulian. The study adopts a qualitative research methodology, focusing on the participation of all students in class VC during September. The research examines how the PjBL method allows students to engage actively in learning by completing projects related to PAI material, such as constructing prayer models or creating reports on Islamic ethics in daily life. The integration of the question-and-answer method plays a crucial role in clarifying students' understanding of complex material while encouraging critical thinking through interaction and dialogue. Data were collected through classroom observations, interviews with teachers and students, and analysis of student project work and reflections. Observations revealed that students showed increased enthusiasm and participation during lessons, especially when given the opportunity to work on meaningful projects that applied religious teachings to real-life contexts. Teachers acknowledged that the question-and-answer method helped in identifying students' difficulties and allowed immediate clarification, leading to better understanding and active classroom interaction. Interviews with students indicated that they found the PjBL approach more engaging and practical compared to traditional learning methods. They expressed that they could better understand and apply the religious concepts they learned because of the hands-on nature of the projects. However, some challenges were noted, particularly for students who were more passive or shy, as they found it difficult to engage fully in group discussions and the question-and-answer sessions. The teachers recognized this issue and made efforts to encourage these students to participate more actively in the learning process. Overall, the research concluded that the combination of Project Based Learning and the question-and-answer method significantly improved student learning outcomes. It fostered a more active and engaging learning environment, enhanced students' understanding of the material, and developed critical thinking and collaboration skills. Although there were challenges, such as time management for project completion and ensuring equal participation among students, the overall effectiveness of this teaching approach was evident. The study suggests that this method can be applied as an alternative strategy in teaching Islamic Religious Education or other subjects that require practical and interactive learning at the elementary school level.